Aren’t you tired of the pandemic yet? - Belloube, Yuri (Universidade Estadual Paulista (Unesp), 2020)
In this episode of the Foreign Language Learner Podcast, a student in the second year of Language Studies at Unesp - São José do Rio Preto talks about living in the Covid19 pandemic and politics during it.
Nível de proficiência de produção oral autoavaliado pelo aluno: B2
Keywords: COVID19 Pandemic; English language Pronunciation by foreigners; Polítics; COVID-19; Pandemias; Língua inglesa Pronúncia estrangeira; Políticas